2012
DOI: 10.5740/jaoacint.11-415
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Chlorogenic Acid and Hyperoside Directly from Crude Blueberry (Vaccinium angustifolium) Leaf Extract by NMR Spectroscopy Analysis: Single-Laboratory Validation

Abstract: A single-laboratory-validated NMR spectroscopy method was established for determining the quantity of chlorogenic acid and hyperoside from crude extract material of blueberry leaves of the species Vaccinium angustifolium var. laevifolium House. The calibration curve of chlorogenic acid showed a highly linear regression, R = 0.99998. NMR spectroscopy identification and quantification of the constituents directly from the mixture, within the error of HPLC-diode array detector analysis, were determined as 7.53 mM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…Hyperoside is quercetin-3-O-galactoside. It was found out in strawberries [Bagdonaite et al 2013], blueberries [Hicks et al 2012], whitethorn [Belkhir et al 2013] and rowan [Gaivelyte et al 2013]. Among herbs, it is abundant above all in St John's wort [Cirak et al 2013].…”
Section: Resultsmentioning
confidence: 99%
“…Hyperoside is quercetin-3-O-galactoside. It was found out in strawberries [Bagdonaite et al 2013], blueberries [Hicks et al 2012], whitethorn [Belkhir et al 2013] and rowan [Gaivelyte et al 2013]. Among herbs, it is abundant above all in St John's wort [Cirak et al 2013].…”
Section: Resultsmentioning
confidence: 99%
“…Chlorogenic acids accumulate in leaves and fruits where they act as feeding deterrents and antifungal agents. They also have potent antioxidant properties which have been shown to protect crops from intense UV radiation damage (Mondolot et al ., ; Cle et al ., ; Hicks et al ., ). Chlorogenic acids are derived through conjugation of quinate and hydroxycinnamoyl moieties (Lallemand et al ., ; Escamilla‐Treviño et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…The presence of several major phenolic compounds in the crude leaf extract reported by McIntyre et al (), Hicks et al (), and Ferrier et al () was reconfirmed using UPLC–QTOF–MS. The phenolic compounds reconfirmed in the extract include chlorogenic acid, myricetin, and hyperoside (Table ).…”
Section: Resultsmentioning
confidence: 68%
“…Vaccinium extracts, including those from V. angustifolium, are a rich source of phenolic compounds (Harris et al, 2007;Hicks et al, 2012;Markus et al, 2014;McIntyre et al, 2009) and have been shown to influence cell migration and invasion using in vitro models of cancer metastasis (Adams et al, 2010;Matchett, MacKinnon, Sweeney, Gottschall-Pass, & Hurta, 2005), in vitro models of endothelial cell migration and invasion (Tulio et al, 2012), and animal models of wound healing (Nayak et al, 2010). In this study, the .…”
Section: Discussionmentioning
confidence: 99%